Interpretar o enunciado ou dialogar com a enunciação? uma análise sobre processos de leitura no ENEM - Branchini, Camila Sabatin (Universidade Federal de São Carlos, 2014)
This paper discusses the reading concepts that are present on the Enem items, specifically on the tests of Languages, Codes and Their Technologies (LCT), in editions from 2009 to 2013. For this, we adopted as the main theoretical reference of this research the notion of discursive genders, (BAKHTIN, 2010; 2011; MARCUSCHI, 2005) the concept of enuciate and enunciation (BAKHTIN, 2010; BRAIT, 2012; FLOWERS, 2009; GERALDI, 1993) as a basis to substantiate the reading conceptions (BAKHTIN, 2010; GERALDI, 2010; KLEIMAN, 1989; 2006; MARCUSCHI, 2005; Matrix Reference Enem, 2009; FREIRE, 1997; ROJO, 2004.) To support the goals of the Enem test as an instrument of government review, we did a recap of the structure and objectives of the Enem evaluation, through the notion of competence and skill as part of a historical, social, political and economic context that enter politics public in education and become part of the official discourse of the documents (LDB, PCN, PCNE). Contextualization that makes clear how changed the way of evaluate. Others researches has hunched on this content, it points to the relevance of the chosen corpus. Launch a new look, new readings on the corpus, shows the need for ever more clearly the social importance of Enem forming a new way to evaluate We have chosen, for that, two items of each year, starting in 2009, when the advent of the New Enem, to 2013, last evaluation. This choice had as criterions issues related to mother language which utilizes the genders as basis for discussion on the enounced of the questions in the test. From a theoretical-methodological assumptions, regarding the form of analysis developed within the humanities, allowed us to analyze the corpus by the perspective of sociological method and/or Bakhtin's discourses and Ginzburg qualitative method (the paradigm called evidentiary). Were made hipoteses about the interpretive walk performed by the candidates at the time they read the enounced of the objective questions proposed on Enem test. From the analyzed editions, we adopted as corpus 10 items of the LCT test which works issues related to mother language. Then, we trace an overview of the types of reads that the candidate/reader made over five years of evaluation, considering that it depends of some elements, such as how they prepared the enounced of the item, the enunciative context, previous knowledge of the candidate. We conclude that the evaluative profile of ENEM tends to approach the reading under the bias of linguistic structure, grammaticalized, often part of the theme, and a few times, considers the enunciation, the dialogue, the interaction, ie, the discursive bias.
Keywords: Leitura; Gêneros discursivos; Dialogismo; Enunciação; Políticas públicas; Exame Nacional do Ensino Médio (ENEM); Método discursivo; Paradigma Indiciário; Public policy of education; Enem; Gender discursive; Enunciation; Reading; Dialogism; Speech; Discursive method; Evidential paradigm; LINGUISTICA, LETRAS E ARTES::LINGUISTICA